El rol del Trabajador Social en el área oncológica: una perspectiva resiliente ante la familia del paciente. - Aguilar Párraga, Evelyn Stefanía (2024)
The objective of this article in this research was to analyze the role of the social worker in the area of oncology and their resilient perspective towards the family of the oncology patient. The method used had a qualitative approach, with a narrative research design. The sample was made up of two social workers from the SOLCA Social Work department and five relatives of oncology patients who receive support from said department. As a data collection instrument, a semi-structured interview guide was applied, valid by expert judgment. The general results revealed that the role of the social worker in oncology is to provide emotional support, guidance, access to resources and humanized and comprehensive care to the patient and her family, constituting an invaluable contribution to improving her quality of life. Likewise, the strong emotional and economic impact that the disease generates on families was evident. It was concluded that the intervention of the social worker in oncology is essential for accompaniment, emotional support, access to resources, coordination with the medical team and promotion of patient rights, being their essential work to humanize health care.